Occupational stress and its influence on employee performance and health outcomes: An empirical analysis across institutional sectors in Islamabad - Shahzadi, Shazia; Mahar, Sourath; Mahar, Abdul Qayoom; Bux, Khuda; Ali, Liaquat (2025)
This study examined the psychological, physiological, and performance-related impacts of occupational stress on human resources across various sectors, with a particular focus on employees in institutions at Islamabad. Prior research has highlighted stress as a significant issue driven by changing social dynamics and lifestyle adjustments, contributing to an understanding of its adverse effects. However, stress does not universally yield negative outcomes; eustress, or "positive stress," has been shown to encourage individuals to confront challenges and reach optimal performance. While much of the existing research has concentrated on the Information Technology and Banking sectors, occupational stress affects employees across all fields. This study aimed to shed light on stress as a widespread and often underappreciated issue and to recommend relevant coping strategies. A survey involving 200 employees was conducted to evaluate job-related, organizational, individual, and physiological reactions to stress and their influence on performance. To analyze the data, descriptive statistics, correlation analysis, and regression analysis were applied, providing a comprehensive understanding of occupational stress effects on employee performance. Cronbach’s alpha was utilized to confirm the survey scale's reliability. The findings suggested that occupational stress moderately impacted employee performance, with job-related stressors, particularly job security, playing a significant role. Physiological reactions to stress, including chronic neck and back pain, fatigue, headaches, and migraines, were also observed to moderately impact performance. These health issues, likely due to prolonged sedentary work hours and negative stress effects, underscored the importance of implementing effective stress management strategies in organizational settings.